(3GdMce GdYWGFjIs - (3GdpErSncrfnOQj, CHh GdaVd, GHf nYnWGA Gddg, JGL GdOjf, CMeO Hf eMeO Hf YHO GdcQje, (B709 (3gs ((3eMeO Hf Ydj GdeGdcjs)
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdNdb hGdJOHjQ hGdhGMO aj GdMce hGdJbOjQ hGdedc GdPj djS dg aj Gdedc hRjQs
(3BNQgG (B:s
(3hCYjf Edi NOeJc eJMbbjf HeYQaJc eJHYjf dQShdc hGQKjf Yfg BNPjf efg heJMbbjf Hg hbGFejf HGdfjGHI Yfg hGNJe defG HNjQ jG QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 221s
(3eYLe GdeDdajf(B: 1 / 275s
(3cTa GdXfhf(B: 1 / 675s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs